Analisis Tingkat Kepuasan Mahasiswa UKSW Terhadap F-Learn Dengan Pendekatan USER EXPERIENCE QUESTIONNAIRE (UEQ) - Edwind Alex Suak; Rudy Latuperissa (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
The rapid development of digital technology has transformed learning systems in higher education, particularly through the implementation of Learning Management Systems (LMS) as the primary platform for online learning. LMS plays an important role in supporting content delivery, academic communication, and flexible learning management. Universitas Kristen Satya Wacana (UKSW) developed an internal LMS called F-Learn as part of its digital learning development strategy. This study aims to evaluate student satisfaction with the F-Learn LMS as a basis for periodic evaluation to support sustainable system development. The study employed the User Experience Questionnaire (UEQ) using a quantitative approach consisting of problem identification, literature review, questionnaire-based data collection, data analysis and discussion, and conclusion formulation. A total of 139 active UKSW students participated as respondents. The results indicate that all UEQ variables fall into good and above-average categories, with dependability achieving the highest score (1.61), followed by efficiency (1.59) and perspicuity (1.56). However, stimulation (1.13) and novelty (1.09) recorded the lowest scores, indicating limited engagement and innovation. In conclusion, F-Learn adequately fulfills functional user needs, but improvements in interface design, content diversity, and interactive features are required to enhance the overall learning experience sustainably.